2015
DOI: 10.1039/c4tc02327g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapour deposition of antimony chalcogenides with positional and orientational control: precursor design and substrate selectivity

Abstract: A series of alkylchalcogenostibines have been synthesised and employed as precursors for the chemical vapour deposition of Sb2Te3 and Sb2Se3. Variations in substrate and temperature give different film morphologies, and patterned arrays can be deposited using substrate selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 42 publications
(48 reference statements)
5
45
0
Order By: Relevance
“…(MO)CVD growth of single‐crystals platelets with partially controlled dimensions and orientation in arrays was reported in refs. . Here it is shown that the same level of crystal quality is reproduced on a pillar, rather than platelets geometry, and in a density that exceeds by orders of magnitude those reported in the above‐mentioned references.…”
Section: Resultssupporting
confidence: 68%
“…(MO)CVD growth of single‐crystals platelets with partially controlled dimensions and orientation in arrays was reported in refs. . Here it is shown that the same level of crystal quality is reproduced on a pillar, rather than platelets geometry, and in a density that exceeds by orders of magnitude those reported in the above‐mentioned references.…”
Section: Resultssupporting
confidence: 68%
“…Energy dispersive X-ray spectroscopy (EDX) spectra also show the presence of Sb and Se peaks ( Fig S2a), and the Raman spectrum indicates a pure Sb 2 Se 3 phase ( Fig S2b). (11) In order to evaluate if Sb 2 Se 3 could be employed as a photocathode for hydrogen evolution, the band positions of the Sb 2 Se 3 were determined using Mott-Schottky (M-S) analysis. To circumvent frequency dispersion in the M-S plots, the space charge capacitance (C SC ) was determined by electrochemical impedance spectroscopy (EIS).…”
Section: Main Textmentioning
confidence: 99%
“…40 Sb 2 Se 3 was also synthesized by alkylselenostibines and selenourea complexes. 41,42 However selenostilbines require toxic metal alkyl compounds for their synthesis, phosphorus based complexes may lead either to phosphorus contamination or formation of an entirely different phosphate product. 24 Similarly, diselenocarbamate precursors has been used for metal selenide thin films but the synthesis requires the use of highly toxic carbon diselenide (CSe 2 ).…”
Section: Introductionmentioning
confidence: 99%